Frontotemporal Dementias in Latin America: History, Epidemiology, Genetics, and Clinical Research - Llibre-Guerra, Jorge J.; Behrens, Maria Isabel; Hosogi, Mirna Lie; Montero, Lucia; Torralva, Teresa; Custodio, Nilton; Longoria-Ibarrola, Erika Mariana; Giraldo-Chica, Margarita; Aguillón, David; Hardi, Angela; Maestre, Gladys E.; Contreras, Valeria; et al. (Frontiers in Neurology, 2021)
Introduction: The historical development, frequency, and impact of frontotemporal dementia (FTD) are less clear in Latin America than in high-income countries. Although there is a growing number of dementia studies in LatAm, little is known collectively about FTD prevalence studies by country, clinical heterogeneity, risk factors, and genetics in LatAm countries. Methods: A systematic review was completed aimed to identify the frequency, clinical heterogeneity, and genetics studies of FTD in LatAm populations. The search strategies used a combination of standardized terms for FTD and related disorders. In addition, at least one author per LatAm country summarized the available literature. Collaborative or regional studies were reviewed during consensus meetings. Results: The first FTD reports published by LatAm were mostly case reports. The last two decades marked a substantial increase in the number of FTD research in LatAm countries. Brazil (165), Argentina (84), Colombia (26), and Chile (23)are the countries with the larger numbers of FTD published studies. Most of the research has focused on clinical and neuropsychological features (n=247), including the local adaptation of neuropsychological and behavioral assessment batteries. However, there are little to no large studies on prevalence (n=4), biomarkers (n=9), or neuropathology (n=3) of FTD. Conclusions: Future FTD studies will be required in LatAm, albeit with a greater emphasis on clinical diagnosis, genetics, biomarkers, and neuropathological studies. Regional and country-level efforts should seek better estimations of the prevalence, incidence, and economic impact of FTD syndromes.